Peranan Sistem dan Prosedur Penjualan terhadap Efektivitas Pengendalian Intern Piutang Studi Kasus pada PT. Sinar Sosro Cabang Bogor - Pamungkas, H. Bambang; Oktaviani, Silvi (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2006)
Every company has different standard, it depends on the determined of policy, but Sinar Sosro Ltd. Utilizes evaluation standard and internal control as general. The mentioned control based on result the company achieved and it has been managed well, such as selling bonus and selling percentage each month. From the existing matters, it can be concluded that selling system and procedure conducted by Sinar Sosro Ltd. has been suitable to practice of good internal control for the sake of activity smoothness. Keywords: Internal control, Credit